Key Challenges and Recommendations for In Vitro Testing of Tobacco Products for Regulatory Applications: Consideration of Test Materials and Exposure Parameters. Issue 1 (January 2023) - Moore, Martha M.; Abraham, Irene; Ballantyne, Mark; Behrsing, Holger; Cao, Xuefei; Clements, Julie; Gaca, Marianna; Gillman, Gene; Hashizume, Tsuneo; Heflich, Robert H.; Hurtado, Sara; Jordan, Kristen G.; et al.
The Institute for In Vitro Sciences (IIVS) is sponsoring a series of workshops to identify, discuss and develop recommendations for optimal scientific and technical approaches for conducting in vitro assays, to assess potential toxicity within and across tobacco and various next generation nicotine and tobacco products (NGPs), including heated tobacco products (HTPs) and electronic nicotine delivery systems (ENDS). The third workshop (24–26 February 2020) summarised the key challenges and made recommendations concerning appropriate methods of test article generation and cell exposure from combustible cigarettes, HTPs and ENDS. Expert speakers provided their research, perspectives and recommendations for the three basic types of tobacco-related test articles: i) pad-collected material (PCM); ii) gas vapour phase (GVP); and iii) whole smoke/aerosol. These three types of samples can be tested individually, or the PCM and GVP can be combined. Whole smoke/aerosol can be bubbled through media or applied directly to cells at the air–liquid interface. Summaries of the speaker presentations and the recommendations developed by the workgroup are presented. Following discussion, the workshop concluded the following: that there needs to be greater standardisation in aerosol generation and collection processes; that methods for testing the NGPs need to be developed and/or optimised, since simply mirroring cigarette smoke testing approaches may be insufficient; that understanding and quantitating the applied dose is fundamental to the interpretation of data and conclusions from each study; and that whole smoke/aerosol approaches must be contextualised with regard to key information, including appropriate experimental controls, environmental conditioning, analytical monitoring, verification and performance criteria.